Estratégias de alfabetização na escola municipal ativa integral (EMAI) José Peregrino de Carvalho no Município de João Pessoa PB - Macena, Williane da Silva (2025)
The aim is to create a virtual booklet of pedagogical literacy strategies as a technical/educational product based on the perceptions of these literacy strategies used by professionals at the José Peregrino de Carvalho Municipal Comprehensive Active School in the city of João Pessoa, Paraíba. It is characterised as applied and descriptive research, using a combined approach (quantitative and qualitative) to analyse the data. The data collection instrument used was a questionnaire, applied to representatives of the school community: support team, learning coordinator, financial administrative coordinator, pedagogical coordinator, protagonist teachers, guided study teachers and class reference teacher. The aim is to produce a booklet of pedagogical strategies for literacy as a technical/educational product with suggestions for pedagogical strategies for literacy, presented in a practical and structured way. The results indicate that although various practices are being implemented, there are still challenges to be faced with regard to meeting the individual needs of students, more specifically those who have learning difficulties.The conclusion is that the production of the booklet proved to be an effective strategy, not just as a technical/educational product, but as a practical and training support tool for educators. However, the involvement and commitment to carrying out learning strategies with students must be collective, bearing in mind that literacy is not the isolated task of a single professional, but rather an articulated, collective and continuous effort.